Regulatory T-Cell Development in the Human Thymus - Caramalho, Íris; Nunes-Cabaço, Helena; Foxall, Russell B.; Sousa, Ana E. (Frontiers in Immunology, 2015)
The thymus generates a lineage-committed subset of Regulatory T-cells (Tregs), best identified by the expression of the transcription factor FOXP3. The development of thymus-derived Tregs is known to require high avidity interaction with MHC-self peptides leading to the generation of self-reactive Tregs fundamental for the maintenance of self-tolerance. Notwithstanding their crucial role in the control of immune responses, human thymic Treg differentiation remains poorly understood. In this mini-review we will focus on the developmental stages at which Treg lineage commitment occurs, and their spatial localization in the human thymus, reviewing the molecular requirements, including TCR and cytokine signalling, as well as the cellular interactions involved. An overview of the impact of described thymic defects on the Treg compartment will be provided, illustrating the importance of these in vivo models to investigate human Treg development.